Brillouin frequency shift measurement with virtually controlled sensitivity. (31st May 2017) - Tanaka, Yosuke; Ozaki, Yuta
Abstract: We propose measuring the change in Brillouin frequency shift (BFS) in an optical fiber with virtually controlled sensitivity based on the Vernier effect using a multimode pump and probe light. We measure BFS from the envelope curve of the spectra for multimode Stokes light without scanning the probe frequency. The sensitivity of BFS is virtually controlled by changing the difference in the mode spacing between the pump and the probe. It is experimentally demonstrated that the virtual sensitivity is controlled from −1.1 to 1.1 GHz/K, the maximum value of which is 1, 100 times higher than the standard BFS of 1 MHz/K.